Policy Brief: Better Data for Breast Cancer in Libya - Alferis , Tariq (Libyan Journal of Public Health Practices, 2024)
Breast cancer represents a growing health challenge in Libya, where data management gaps hinder effective diagnosis, treatment, and research efforts. This policy brief highlights the urgent need for a consolidated data framework to improve the quality and accessibility of breast cancer data across the country. Through standardized data collection protocols and a centralized database, healthcare professionals can better monitor trends, enabling early diagnosis and timely interventions. The proposed approach includes training healthcare personnel in data management best practices and establishing a multi-stakeholder steering committee to oversee data governance, privacy, and security. By addressing these issues, Libya can enhance breast cancer treatment outcomes, support evidence-based policymaking, and contribute to international research efforts. This initiative underscores the critical role of data-driven approaches in advancing public health and improving patient outcomes.